Digital Transformation for MSME Resilience in The Era of Society 5.0 - Utami Putri, Aulia; Mirani, Dwi; Khairunnisyah, Tuty (Indonesian Association for Public Administration (IAPA), 2023)
The purpose of this paper is to discuss the effect of digital transformation on the resilience of MSMEs in the era of society 5.0 in Palembang City and determine the digital adoption rate among MSMEs, identify barriers to digital transformation, understand factors behind MSMEs' success or failure in the digital transition. The use of digital transformation certainly has an impact on both MSME players and consumers, who get convenience and are able to survive in the era of society 5.0. In this paper, researchers used quantitative analysis and linear regression analysis with the help of SPSS 22. The population in this study was 1,103 MSMEs in Palembang City, with a sample size of 110 MSMEs. The results of the research obtained using the t test and F test show that digital transformation has a positive and significant effect on the resilience of MSMEs. The magnitude of the relationship or correlation value obtained from the data is 60.2%, which can be explained by business actors carrying out data- based digital transformation, adopting a work culture, determining a simple roadmap, digital awareness, and an environment that supports the success of digital transformation, while the remaining 40.8% can be explained by the influence of other variables not examined by the author. Digital Transformation Challenges for MSMEs, such as Capital Limitations, Lack of Technology Knowledge, Lack of Trained Human Resources, Cyber Security Issues, Business Model Changes, Reliance on Third-Party Platforms, and Integration Difficulties with Legacy Systems, Cultural Adaptation Challenges, and Infrastructure In the future, this research can provide a comprehensive understanding of MSMEs' digital transformation landscape. Recommendations for MSMEs to harness digital opportunities and policy suggestions for governments to support MSMEs in their digital journey